Using Polyurethane Coating of Concrete Pipes with Acid Attack Resistance in Sewer Lines - H. Ismail, Alhassan; Sh. Abed, Basim (International Journal of Engineering and Technology, 2018)
One of the most important challenges facing the designers of the sewerage system is the corrosion of sewers due to the influence of sewerage contaminates which lead to failure of the main lines of sewers. In this study, a reference mix of 1: 1.5: 3 was used and the 4% Flocrete PC200 by weight of cement was added to the same mixing ratio in the second mixture. Twenty-four samples were tested for each mixture, 12 of which were used to compression strength test in ages (7, 14 and 28) day and six samples were submerged after 28 days of wet treatment at (5 and 10) % concentrations of sulfuric acid. The other six samples were painted after 28 days of wet treatment with coating Polyurethane and after 24 hours were flooded with a concentration of (5 and 10) % of sulfuric acid. The results showed that the specimens coated with polyurethane paints, whether they were referenced or added 4% Flocrete PC200, were very high resistance to corrosion, where the weight loss ratio was 0%.